2015
DOI: 10.1016/j.neubiorev.2015.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone signaling: Contribution to neural function, cognition, and relationship to nicotine

Abstract: Cigarette smoking is common despite its adverse effects on health, such as cardiovascular disease and stroke. Understanding the mechanisms that contribute to the addictive properties of nicotine makes it possible to target them to prevent the initiation of smoking behavior and/or increase the chance of successful quit attempts. While highly addictive, nicotine is not generally considered to be as reinforcing as other drugs of abuse. There are likely other mechanisms at work that contribute to the addictive lia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 138 publications
0
4
0
1
Order By: Relevance
“…Several studies found higher T3 levels in smokers (54). Smoking is associated with hyperthyroidism and negatively associated with hypothyroidism (55) and the prevalence of subclinical hypothyroidism was markedly reduced among smokers (56).…”
Section: Negative Associationsmentioning
confidence: 98%
“…Several studies found higher T3 levels in smokers (54). Smoking is associated with hyperthyroidism and negatively associated with hypothyroidism (55) and the prevalence of subclinical hypothyroidism was markedly reduced among smokers (56).…”
Section: Negative Associationsmentioning
confidence: 98%
“…Experimental induction of hypothyroidism produces a rapid reduction in hippocampal neurogenesis [372,373]. This is accompanied by selective impairments on tests of HDLM-effects that are well established and replicable [374]. In sum, for humans, there is good evidence for hippocampal impairment in clinical hypothyroidism, but it is unclear if this is first or foremost.…”
Section: Hypothyroidismmentioning
confidence: 99%
“…Hippocampal neurogenesis is thought to play a role in memory, and this may be the mechanism by which thyroid hormone levels influence cognition (21). It has been suggested that thyroid hormone may control the expression of ChAT, the gene responsible for acetylcholine synthesis (22). Hashimoto's encephalopathy is a controversial and poorly understood condition characterised by cognitive dysfunction (in addition to seizures, movement disorders and neuropsychiatric symptoms) associated with thyroid peroxidase antibodies in patients who are euthyroid (23).…”
Section: Cognition and Other Endocrine Disordersmentioning
confidence: 99%